A review on recycled concrete aggregates (RCA) characteristics to promote RCA utilization in developing sustainable recycled aggregate concrete (RAC). Issue 13 (28th September 2022) - Danish, Aamar; Mosaberpanah, Mohammad Ali
Abstract: Nowadays, sustainable construction materials are becoming popular in the construction industry. The path towards sustainability development indicates minimisation of environmental impacts of the construction industry. In the view of this, increased environmental and financial concerns related to dumping construction and demolished waste (C&DW), using recycled concrete aggregates (RCA) as a replacement (partial or full) of natural aggregates (NAs) are getting appreciable attention in the construction industry. This review article comprehensively discusses the production, properties and enhancement methods of RCA. This article also documents the microstructure and properties of recycled aggregate concrete (RAC) and methods to improve its performance.